Effects of insulin-induced hypoglycaemia on the fate of glucose carbon atoms in the mouse - Vrba, R. (1966)
1. [U-(14)C]Glucose was injected into mice and the distribution of (14)C in various chemical fractions of the whole body was determined at times from 15min. to 8hr. after injection. 2. At 1hr. after injection 31·8% of the recovered (14)C was found in the expired air and 26·7% was found in the isolated glycogen, lipids, proteins, nucleic acids and in other acid-insoluble carbon compounds (`residual (14)C'). The rest (41·5%) was combined in acid-soluble substances. 3. When insulin was injected 5min. or 1hr. before injection of [U-(14)C]glucose, and the mouse was killed 1hr. later, the (14)C content of expired air, glycogen, protein and `residual (14)C' was not significantly affected; but the incorporation of (14)C into lipids was increased two- to three-fold. 4. Chromatography of the lipids on silicic acid columns and by thin-layer chromatography showed that the main effect of insulin injection was to increase the incorporation of (14)C into fatty acids. 5. A significant increase of (14)C after insulin injection was also found in a glyceride in which the (14)C was combined in glycerol.